Efektivitas Hukum Adat Terhadap Pencegahan Pencurian Kelap Sawit Di Tinjau Dari Fiqh Siyasah (Studi Kasus Desa Balimbing Kabupaten Mandailing Natal) - Rahmadani, Rahmadani; Siregar, Khoiruddin Manahan; Gunawan, Hendra (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The aim of this research, first, is to find out what forms of customary sanctions are imposed on perpetrators of palm oil theft in Balimbing Village, Natal District, Mandailing Natal Regency. Second, the level of effectiveness of Balimbing Village customary sanctions in preventing palm oil theft. Third, a review of Islamic law regarding customary sanctions in Natal District for perpetrators of Palm Oil Theft. The method used in this research is a qualitative descriptive method using field data (field research). Balimbing Village, Natal District, in resolving the dispute was resolved according to custom through a deliberation process. Then the palm oil thief is required to apologize to the entire community of Balimbing Village and return the stolen goods or replace them in the form of money according to what he stole, and also in return for his actions he is charged